Puberty arises with testicular alterations and defective AMH expression in rams prenatally exposed to testosterone - Recabarren, S. E. (2017)
The male gonadal tissue can be a sensitive target to the reprogramming effects of testosterone (T) during prenatal development. We have demonstrated that male lambs born to dams receiving T during pregnancyda model system to the polycystic ovary syndrome (PCOS)d show a decreased number of germ cells early in life, and when adult, a reduced amount of sperm and ejaculate volume. These findings are a key to put attention to the male offspring of women bearing PCOS, as they are exposed to increased levels of androgen during pregnancy which can reprogram their reproductive outcome. A possible origin of these defects can be a disruption in the expression of the anti-Müllerian hormone (AMH), due to its critical role in gonadal function at many postnatal stages. Therefore, we addressed the impact of prenatal T excess on the expression of AMH and factors related to its expression like AP2, SOX9, FSHR, and AR in the testicular tissue through real-time PCR during the peripubertal age. We also analyzed the testicular morphology and quantified the number of Sertoli cells and germ cells to evaluate any further defect in the testicle. Experiments were performed in rams at 24 wk of age, hence, prior puberty. The experimental animals (T-males) consisted of rams born to mothers receiving 30 mg testosterone twice a wk from Day 30 to 90 of pregnancy and then increased to 40 mg until Day 120 of pregnancy. The control males (C-males) were born to mothers receiving the vehicle of the hormone. We found a significant increase in the expression of the mRNA of AMH and SOX9, but not of the AP2, FHSR nor AR, in the T-males. Moreover, T-males showed a dramatic decrease in the number of germ cells, together with a decrease in the weight of their testicles. The findings of the present study show that before puberty, T-males are manifesting clear signs of disruption in the gonadal functions probably due to an alteration in the expression pattern of the AMH gene. The precise way by which T reprograms the expression of AMH gene remains to be established.